Anti-Inflammatory Mechanisms of Fucoidans to Treat Inflammatory Diseases: A Review - Kalu K. Asanka Sanjeewa; Kalahe H. I. N. M. Herath; Hye-Won Yang; Cheol Soo Choi; You-Jin Jeon (Marine Drugs, 2021)
Fucoidans are sulfated heteropolysaccharides found in the cell walls of brown seaweeds (Phaeophyceae) and in some marine invertebrates. Generally, fucoidans are composed of significant amounts of L-fucose and sulfate groups, and lesser amounts of arabinose, galactose, glucose, glucuronic acid, mannose, rhamnose, and xylose. In recent years, fucoidans isolated from brown seaweeds have gained considerable attention owing to their promising bioactive properties such as antioxidant, immunomodulatory, anti-inflammatory, antiobesity, antidiabetic, and anticancer properties. Inflammation is a complex immune response that protects the organs from infection and tissue injury. While controlled inflammatory responses are beneficial to the host, leading to the removal of immunostimulants from the host tissues and restoration of structural and physiological functions in the host tissues, chronic inflammatory responses are often associated with the pathogenesis of tumor development, arthritis, cardiovascular diseases, diabetes, obesity, and neurodegenerative diseases. In this review, the authors mainly discuss the studies since 2016 that have reported anti-inflammatory properties of fucoidans isolated from various brown seaweeds, and their potential as a novel functional material for the treatment of inflammatory diseases.